Function of Urban Space in strengthen social interaction through Time - Ebraheem, Mustafa Abduljalil; Ahmed, Zainab Abbas (Journal of Planner and Development, 2020)
problem of the research is the decline of the role of urban space with time as an influential system in societal relations. The research aims to define indicators for achieving social interaction in the city, and to determine indicators for achieving integration in the urban space, and to study the relationship between the integration of urban space and community interaction over time. the research assumed that by distinguishing the social interaction space from the urban space and developing urban spaces in order to be truly interactive spaces, this will help us achieve social interaction and build a positive relationship between them, which enables us to achieve integration within the urban spaces leading to social interaction. Because the current trend that many have noticed is the diminution of these urban spaces rather than their extension. As a general methodology for the research, the descriptive analytical method was adopted, and people were polled about the urban spaces chosen from the study area, and the GIS program was used to map and analyze maps through satellite images for three years different from the study area. The theoretical framework of the research included four chapters. In the first chapter. The concept of space, place, public spaces and its planning and social interactions in urban public places were reviewed. As for the second chapter, the concept of social interaction, the results of social interaction, and the theories explaining the processes of social interaction, social interaction, environment and time are explained. The third chapter is about time, its definition, its philosophy and the sense of it and time and space. As for the practical framework for the research, which represented the last chapter is a survey of the       selected places in the study area. The research reached the following main conclusions: • The presence of multiple activities such as commercial, cultural and recreational activity and the presence of restaurants and cafes on the Inner Karrada Street led to an urban gathering, and a large daily communicational and social interaction in this street and from all segments of society and residents of the eastern Karrada region and residents of all areas of the city of Baghdad as well as from the provinces of Iraq.  • There is significant overlap and compactness of land uses in the study area, such as residential use with commercial, industrial, educational, health, administrative, and other uses, due to the importance of the study area and the importance of its strategic location as it is in the center of Baghdad.